Survival Strategy of Convensional Micro, Small and Medium Enterprises (MSMEs) Based on “Toto Kromo” Values in the Digital Age - Salleh, Abdul Muizz Mohd; Hulwati, Hulwati; Wira, Ahmad; Rozalinda, Rozalinda; Helmalia, Helmalia; Indriani, Novia (Yayasan Irwan Abdullah Cendekia, 2024)
Survival based on the values of “Toto Kromo” is a strategy that is not least performed by Micro, Small and Medium Enterprises (SMEs) to survive and exist in the digital era. However, this strategy has not been comprehensively discussed in previous studies.This study also focuses on the question “How is the survival strategy based on the values of “Toto Kromo” applied by conventional SMEs to survive amid the massive online-based buying and selling activities in the digital era?” In order to answer this question, this study uses a descriptive qualitative approach in exploring communication, service, and economic transaction strategies carried out by conventional MSMEs in the digital era. This study highlights three important strategies carried out by conventional MSMEs based on “Toto Kromo” values to survive and exist in the digital era. First, the communication is more persuasive, relational, and interactive with buyers. Second, the services are more solutive, active, and supportive with buyers. Third, transactions are more negotiative, accommodating, and effective with buyers.